Halsbury's Laws of Singapore: Vol. 6(2): Conflict of Laws - YEO, Tiong Min (Institutional Knowledge at Singapore Management University, 2020)
This volume discusses conflicts of law, divided into three segments, namely jurisdiction (nine chapters in total), foreign judgements (consisting of four chapters) and choice of law (discussed in three chapters).